Evaluation of the LTD program on the psychological development in athletes - McLean, M. (University of Calgary, 2023)
The Long-Term Development (LTD) model is utilized by multiple National Sport Organization (NSO) to aid in the development and progression of individuals who partake in physical activity. The LTD model consists of 7 stages (Active Start; FUNdamentals; Learn to Train; Train to Train; Train to Compete; Train to Win; Active for Life) which track and progress various skills during target training times to aid in improving performance. The LTD model works on developing five elements of sport which consists of physical, technical, tactical, psychological, and emotional skills. Under the current LTD model, there lacks research on the Psychological Skills Training (PST) that are implemented throughout the stages of development. A content analysis was conducted to determine upper level categories in regards to PST for determining the type of psychological skills being prescribed at the Train to Train; Train to Compete; Train to Win stages. Twelve upper level categories were found through this content analysis 1) Individual Psychological Preparation, 2) Psychological Skills Development, 3) Competition Plans & Routines, 4) External Factors, 5) Arousal, Anxiety and Stress Management, 6) Communication, 7) Sport Enjoyment, 8) Self-Talk, 9) Goal Setting, 10) Imagery/Visualization, 11) Teamwork Components, 12) Focus/Refocus. An evaluation of these categories and the progression between the stages being analyzed were shown to have inconsistencies in progression and prescription. An analysis to determine the prevalence of PST in various sport types (Individual; Team; Combative; Artistic) was also completed. Findings show a lack of regularity in PST recommendation throughout both stages and sport types. Intentional practice and consistency should be advised to ensure adequate understanding and utilizing PST.